Case Report: Should Regorafenib be prescribed as a continuous schedule in gastrointestinal stromal tumors? Three case reports on Regorafenib personalized schedule - Grimaudo, Maria Susanna; Laffi, Alice; Gennaro, Nicolò; Fazio, Roberta; D’Orazio, Federico; Samà, Laura; Siracusano, Licia Vanessa; Sicoli, Federico; Renne, Salvatore Lorenzo; Santoro, Armando; Bertuzzi, Alexia Francesca (Frontiers in Oncology, 2023)
Introduction: Regorafenib is a tyrosin kinase inhibitor (TKI) approved in metastatic GIST, colorectal cancer and hepatocarcinoma. Anyway, the toxicity profile of Regorafenib standard schedule is associated to a poor compliance and high rate of discontinuation. For this reason, the need of a Regorafenib schedule personalization has been arisen among the scientific community. Objective: The aim of this case series was to describe the experience of our sarcoma referral Center on a continuous administration of Regorafenib as an alternative regimen to treat metastatic GIST patients. Methods: We retrospectively collected clinical, pathological and radiological data of patients with metastatic GIST treated with daily personalized Regorafenib at a single tertiary referral Center from May 2021 to December 2022. Results: We identified 3 patients fulfilling the inclusion criteria. The average follow-up since the start of Regorafenib was 19.1 months (12 - 25 months). All 3 had started a standard Regorafenib schedule in third line according to guidelines. The reasons for switching to a continuous schedule were: symptoms exacerbation during week-off treatment in the first patient, a serious adverse event (AE) in the second patient, and a combination of both conditions in the third. After switching, none of the patients reported severe AEs, and they improved control of tumor-related symptoms. Two of the patients experienced disease progression after 16 months (of which 9 months of continuous schedule) and 12 months (of which 8.1 months of continuous schedule) of Regorafenib, respectively; the third patient is still receiving continuous Regorafenib at the time of writing, with a progression-free survival of 25 months (13 months after the modified schedule start). Conclusion: With a similar efficacy and lower toxicities, a daily, personalized Regorafenib schedule seems to be a promising alternative to the standard regimen for metastatic GIST patients, including the frail ones. Further prospective analyses are needed to confirm safety and efficacy of such regimen.